About the Formation of Ecological Ethics - Kalenda, Česlovas (Problemos, 1996)
The catalyst to the formation of modern ecological ethics was the discussion about the historical sources of the ecological crisis. This discussion took place at the end of the sixties in Western countries, and it initiated a wave of critics of the main principles, especially Christian ones, of the Western worldview. The author of the article discusses the question of the ecologico-moral content of monotheism. He discovers ecophile tendencies in the Christian faith. He reports some facts about the history of the spreading of Christian ideas in Lithuania, which serve as evidence of the education of a positive human attitude toward the natural environment.